Pengaruh Cara Tanam dan Penggunaan Varietas terhadap Produktivitas Wijen (Sesamum indicum L.) - Budi, Luluk Sulistiyo (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2007)
The important strategy to increase the productivity of sesame is intensification program.  One of the possible technique was  the  planting method and  varieties.  This research aimed at determining the correct  planting method and varieties to reach high sesame production. This study used the factorial randomized block design with three replications.  The first factor was the planting method which consisted of three levels, i.e.; Broadcast, Broadcast in wide furrow, and dibbed planting.  The second factor consisted of nine varieties, namely, one superior variety Sbr1 and eight local varietes i.e Magetan, Madiun, Ponorogo, Ngawi, Nganjuk, Kediri, Bojonegoro, and Blora. The result showed that the combination of dibbed planting with Blora and Madiun resulted the highest yield (1.11 ton/ha), but it was not significantly different with the combination of  dibbed planting  with  superior variety Sbr 1. Ponorogo has the highest oil content and the weight of 1000 seeds.  There were positive correlations between oil content and  the weight of 1000 seeds (0.77), between harvesting age and the weight of 1000 seeds (0.66) and between oil content and the harvesting age (0.61).   Key words :  Planting method, local variety,  sesame,  Sesamum indicum  L.